Ki Hadjar Dewantara’s Thought About Holistic Education - et. al., Taufikin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted to determine whether Ki Hadjar Dewantara's educational thought was included in the Holistic category. Therefore, content analysis of the documents of Ki Hadjar Dewantara's works is used in the research. The results showed that Ki Hadjar Dewantara's educational thought was included in the holistic category, such as independence in the exoteric and esoteric dimensions which was described by the achievement of spiritual, intellectual, emotional, physical, social and aesthetic aspects